THE INFLUENCE OF BEAUTY INFLUENCERS AND ONLINE CUSTOMER REVIEWS ON PURCHASE INTENTION OF D’ALBA PRODUCTS IN PALEMBANG CITY - Cia, Lienny; Florensia, Clarisa; Felicia, Sheren (LPPM Univ. Ibn Khaldun Bogor, 2025)
This study investigates the influence of Beauty Influencers (X1) and Customer Reviews (X2) on the Purchase Intention (Y) of d'Alba products in Palembang. A quantitative approach was employed, using structured questionnaires to collect clear and measurable insights into consumer behavior. Respondents were chosen through purposive sampling to ensure that participants were familiar with d'Alba products and actively engaged with the digital platforms where the brand is promoted. The data underwent multiple stages of analysis. Initially, validity and reliability tests confirmed the accuracy and consistency of the measurement instruments. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity checks, were performed to ensure the regression model met all statistical requirements. Multiple linear regression analysis was applied to examine the extent to which Beauty Influencers and Customer Reviews affect purchase intention. T-tests assessed the significance of each independent variable, while the coefficient of determination (R²) measured the proportion of variation in purchase intention explained by these variables. The findings demonstrate that both Beauty Influencers and Customer Reviews have a positive and significant effect on consumers’ purchase intentions for d'Alba products in Palembang. This highlights the crucial role of digital marketing and peer feedback in shaping modern purchasing decisions.